ANALISIS RESERVOAR MIGAS (SANDSTONE) MENGGUNAKAN MULTIATRIBUT SEISMIK PADA LAPANGAN TG12, CEKUNGAN BARITO, KALIMANTAN SELATAN - Edo Pratama; Bagus Sapto Mulyatno; Ahmad Zaenudin (Jurnal Geofisika Eksplorasi, 2019)
The study using multi attribute seismic has been done on TG12 field which situated at Lower Foreland Formation, Barito Basin dominated by sandstone on layer area of the target X. The objective of the study is to map the sandstone reservoir by predict distribution value of gamma ray log, neutron porosity, and density which goes through wells such as FM1, FM2, FM3, and FM4 on seismic data. Total attribute that is being used by step wise regression method by considering validation error. Multiattribute process only applied on FM2, FM3, and FM4 wells, whereas FM1 is used as a test well to determine the correlation value between seismic data and log data that is being used. In addition, from well test correlation showing great correlation result of neutron porosity log and density log both obtain the correlation around 0.6322 and 0.6557 while the gamma ray log obtain low correlation that is 0.1647 towards multi attribute result. The processing result of multi attribute obtained distribution of sandstone with gamma ray estimation range value of 65-75.8API, neutron porosity estimation range value 0.15-0.2262, while density estimation range value 2.4308-2.77gr/cc.